CIVIL SOCIETY INTERACTIONS WITHIN THE INTER-AMERICAN INSTITUTIONAL FRAMEWORK: TWO CASE STUDIES IN PROMOTING THE STRENGTHENING OF THE REGIONAL HUMAN RIGHTS SYSTEM - Lessard, Geneviève (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2011)
This paper is an attempt to partly address the question of the impact, on the inter-American human rights system, of non-state actors interacting within the institutional structure of the Organizations of American States (OAS). It reflects the perspective of Rights & Democracy, a Canadian institution with an international mandate to promote democracy by supporting the full realization of all human rights. Rights & Democracy has supported civil society human rights organizations in their battle for a stronger regional human rights system, and a more participatory OAS. The paper first reviews the formal inter-American structure for civil society participation, then submits what is meant to be an empirical contribution. It describes two concrete civil society participation experiences aiming to strengthen the enforcement of inter-American human rights norms: the ongoing process carried out by the International Coalition of Organizations for Human Rights in the Americas, and the actions undertaken by indigenous peoples within the framework of the negotiations surrounding the Draft American Declaration on the Rights of Indigenous Peoples. The paper ends with some concluding remarks on a mitigated assessment of civil society participatory mechanisms within the OAS.